Improving Teachers' Digital Literacy Through Training in The Preparation of Teaching Modules with The AI Platform - Yakob, Muhammad; Yani, Ahmad Fauzi Syahputra; Putri, Mentari Darma (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to improve the digital literacy of SMP Negeri 1 Rantau Selamat teachers through training in the preparation of teaching modules by utilizing AI technology. The methods used in this PKM activity were planning through surveys and interviews, socialization, and training in the preparation of teaching modules by utilizing AI technology. The socialization and training activities involved 28 teachers of SMP Negeri 1 Rantau Selamat, Aceh Tamiang, Aceh Province as participants. The pretest and post-test results of the participants, namely 74 and 88, respectively, showed an increase in teachers' understanding of the development, potential, and utilization of AI technology in preparing teaching modules for the Merdeka curriculum. The questionnaire results also showed a positive impact on this PKM activity and were shown by the enthusiasm and support of the school for the implementation of this PKM activity.